Digital Ethics as a Preventive Framework for Combating Digital Drug Addiction ''An Analytical Study within the Cyberspace Environment'' - Sharaf, Mohamed (International Journal of Sustainable Development Goals, 2025)
In today's digital age marked by rapid technological change and the remarkable growth of Artificial Intelligence, digital technologies have become deeply integrated into people's daily lives across different societies. Although these technologies were initially created to improve human well-being and advance social progress, their misuse by certain groups has resulted in negative and ethically troubling outcomes. One of the most concerning examples of such misuse is the emergence of digital drugs—auditory or visual stimuli that produce psycho-physiological effects similar to those of traditional narcotics. Even though they are intangible, digital drugs carry risks comparable to those of physical substances, especially when there is a lack of moral discipline, digital responsibility, and social accountability. In this context, the current study aims to explore how digital ethics can serve as a preventive framework to reduce the dangers of digital drug addiction and encourage responsible digital conduct within the larger social and behavioral landscape sciences.